Leishmaniasis: prevention, parasite detection and treatment - Kobets, T; Grekov, I; Lipoldova, M (Current medicinal chemistry, 2012)
Leishmaniasis remains a public health problem worldwide, affecting approximately 12 million people in 88 countries; 50 000 die of it each year. The disease is caused by Leishmania, obligate intracellular vector-borne parasites. In spite of its huge health impact on the populations in vast areas, leishmaniasis is one of the most neglected diseases. No safe and effective vaccine currently exists against any form of human leishmaniasis. The spectrum and efficacy of available antileishmanial drugs are also limited. First part of this review discusses the approaches used for the vaccination against leishmaniasis that are based on the pathogen and includes virulent or attenuated parasites, parasites of related nonpathogenic species, whole killed parasites, parasites' subunits, DNA vaccines, and vaccines based on the saliva or saliva components of transmitting phlebotomine vector. Second part describes parasite detection and quantification using microscopy assays, cell cultures, immunodetection, and DNA-based methods, and shows a progress in the development and application of these techniques. In the third part, first-line and alternative drugs used to treat leishmaniasis are characterized, and pre-clinical research of a range of natural and synthetic compounds studied for the leishmanicidal activity is described. The review also suggests that the application of novel strategies based on advances in genetics, genomics, advanced delivery systems, and high throughput screenings for leishmanicidal compounds would lead to improvement of prevention and treatment of this disease.
Keywords: DNA, Protozoan; Vaccines, DNA; leishmanióza; lidé; Antiprotozoal Agents; DNA vakcíny; mikroskopie; kožní testy; Protozoan Vaccines; Enzyme-Linked Immunosorbent Assay; Animals; Humans; ELISA; zvířata; protozoální DNA; Leishmaniasis; Skin Tests; antiprotozoální látky; Microscopy; protozoální vakcíny; Leishmania